Subtraction Bugs in an Acalculic Patient - Girelli, Luisa; Delazer, Margarete (Cortex, 1996)
We report a patient, MT, who presented a specific, though not isolated, deficit in written calculation. Despite a preserved knowledge of simple arithmetic — single-digit addition and subtraction — he failed systematically in multi-digit subtraction. The nature of errors was consistent across problems and reflected the application of a disturbed underlying algorithm. Moreover, the pattern pf error observed mimics a very common finding in developmental studies on arithmetical procedure acquisition (Fuson, 1990, 1992; Young and O'Shea, 1981; VanLehn, 1986, 1990). The data suggest that, within calculation skills, syntax may exist as a system of stable, but inappropriate, rules which are independent of any underlying conceptual knowledge.